Hubungan Self-Management Pengobatan Terhadap Kadar Gula Darah Pada Pasien Rawat Jalan Diabetes Melitus Tipe 2 Di Puskesmas - Umul Farida; Kumala Sari Poespita D. W; Dianty Putri Millania Paringsih (State University of Gorontalo, 2023)
This study aims to evaluate the relationship between the level of self-management of medication and blood glucose levels in outpatient type 2 diabetes mellitus patients at the Kediri City Health Center. The research falls under the category of quantitative research with an observational study approach, using a cross-sectional design. Diabetes mellitus (DM) is a chronic condition characterized by hyperglycemia and various metabolic abnormalities due to hormonal disorders, which can lead to long-term complications in the eyes, kidneys, nerves, and blood vessels. Data were collected using the DSME Questionnaire (Diabetes Self Management Education) to assess the level of self-management of medication.The results showed that 12 respondents (13.8%) had poor self-management of medication and poor blood glucose control. There were 14 respondents (22.2%) with moderate self-management of medication and uncontrolled blood glucose. Meanwhile, 18 respondents (28.6%) had moderate self-management and blood glucose within the normal range. A total of 31 respondents (49.2%) had moderate self-management and normal blood glucose levels. Only 12 respondents (13.8%) had good self-management and blood glucose within the normal range.The Spearman rank test results indicated a significant relationship between self-management of medication and blood glucose levels in type 2 diabetes mellitus patients. With Î± = 0.05, the obtained P-value was 0.000, which is smaller than 0.05. Therefore, the alternative hypothesis (H1) is accepted, while the null hypothesis (H0) is rejected. This suggests the presence of a relationship between self-management of medication and blood glucose levels, with a Spearman rank correlation coefficient of 0.598.